Analysis of Pipe Water Inlet EW010 Quality Control Using Six Sigma and Failure Mode and Effect Analysis: Case Study: PT Wijaya Karya Industri dan Konstruksi - Fadhlullah, Faris; Noya, Sunday; Putrianto, Novenda Kartika; Oktiarso, Teguh (Teknik Industri Universitas Ma Chung, 2024)
PT Wijaya Karya Industri dan Konstruksi has businesses in the fields of Steel, Plastic, Pressing and Casting (PPC) Manufacturing and heavy construction equipment. The PPC factory produces various kinds of manufacturing components, one of which is vehicle spare parts made from metal which are produced using a casting process. One of the products produced using a casting process is Pipe Water Inlet EW010. There are many Pipes Water Inlet EW010 defective products with an average of 52% defective products in July-August 2023. The research was conducted to analyze the sigma value and determine the factors of product defects and the impact of the defects to provide suggestions for product quality improvement. In this research, the method applied is the Six Sigma method and FMEA, by implementing DMAIC (Define, Measure, Analyze, and Control). From this research, the results showed that the most common defects were Leaking, Pen/core, and Porous, namely 89% cumulative. Pipe Water Inlet EW010 products are currently at level 2.44 sigma so corrective action needs to be taken to reach the six-sigma level. By applying the FMEA method, it can be seen that the most significant and most frequently occurring product defects are caused by poor core quality and work method errors. Therefore, the recommended alternative repair solution is to improve the quality of the cores used and improve work methods. The results show an increase in the sigma level value from 2.44 to 2.86 and a decrease in average defects from 52% to 23%.